Pengaruh Kecerdasan Intelektual, Budaya Organisasi dan Komunikasi Organisasi Terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kota Surakarta - Dinnova Ryo Kristanto; Agus Suyatno; Esti Dwi Rahmawati (Transformasi: Journal of Economics and Business Management, 2024)
Human Resource Management (HRM) is a crucial aspect of organizational management that focuses on managing individuals as valuable assets to the company. One significant area of HRM is job satisfaction, which is a complex emotional reaction to one's job. High job satisfaction can enhance employee performance, as satisfied employees tend to be more enthusiastic and productive. Employee performance, which includes abilities, skills, and work outcomes, can be influenced by intellectual intelligence, organizational culture, and organizational communication. Intellectual intelligence (IQ) plays a role in employees' effectiveness at work and contributes to organizational success. Effective organizational communication strengthens an inclusive culture and supports collaboration, while organizational culture serves as an identity and impacts employee performance. This study aims to analyze the effects of intellectual intelligence, organizational culture, and organizational communication on employee performance through job satisfaction as an intervening variable at the Surakarta City Population and Civil Registration Office. The research is expected to provide insights into how these factors influence employee performance and offer recommendations for enhancing satisfaction and performance within the government organization.